Apakah pendapatan utama dari perkebunan mempengaruhi deforestasi?: Studi dari tingkat desa di Kalimantan, Indonesia - Muhammad Yazid (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2022)
The complexity of the drivers of deforestation in Indonesia requires various research on deforestation, especially to support policies related to reducing deforestation. The economy is one aspect that contributes to providing an overview of deforestation. This study investigates the relationship between deforestation and village with dominant income from plantation as main commodity. A panel data analysis using data from 3260 villagesin Kalimantan in 2011, 2014, and 2018 was analyzed to determine whether plantation as main income affected deforestation. The dependent variable is deforestation in each village. There are 14 independent variables used,with the main variable is villages with main income from plantation as a dummy variable. The results of random effect model show that villages with plantation as main commodity have a positive impact on deforestation.Ten independent variables show a positive relationship with deforestation. Four independent variables show a negative relationship with deforestation, which include the use of firewood, practice of burning land, non-woodsmall industries, and logging companies (PBPH Hutan Alam). The recommendation of this research is the need to replanting the degraded and non-productive land for the wood plantation areas, thus the conversion of forest into non-forest area can be avoided.